2008
DOI: 10.1080/13506280701437295
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor capture by surprising onsets

Abstract: The present study examined the effect of surprising onsets on oculomotor behaviour. Participants were required to execute a saccadic eye movement to a colour singleton target. After a series of trials an unexpected onset distractor was abruptly presented on the surprise trial. The presentation of the onset was repeated on subsequent trials. The results showed that the onset captured the eyes for 28% of the participants on the surprise trial, but this percentage decreased after repeated exposure to the onset. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 24 publications
7
25
0
Order By: Relevance
“…This paradigm was adapted by Godjin and Kramer (2008) to demonstrate oculomotor capture from the first appearance of an abrupt onset distractor. An unexpected stimulus cannot be used as any form of task-relevant signal and therefore would seem irrelevant to any top-down attentional setting.…”
mentioning
confidence: 99%
“…This paradigm was adapted by Godjin and Kramer (2008) to demonstrate oculomotor capture from the first appearance of an abrupt onset distractor. An unexpected stimulus cannot be used as any form of task-relevant signal and therefore would seem irrelevant to any top-down attentional setting.…”
mentioning
confidence: 99%
“…However, regardless of the orienting mechanism at play, the decrease in RTs and number of fixations on the post-critical trials relative to the critical trial demonstrates that stimulus novelty was critical to the effects observed in Experiment 2. These results demonstrate that oculomotor capture was modulated by the first presentation of an unannounced colour singleton, a result that has previously been demonstrated with onset transients (Godijn & Kramer, 2008) but not with colour stimuli.…”
Section: Eye-movement Analysessupporting
confidence: 59%
“…There is some evidence to suggest that unexpected stimuli can still capture attention and the gaze even when the target is pre-attentively available and able to compete for early selection. For instance, Godijn and Kramer (2008) found oculomotor capture by an unannounced new onset distractor when participants had the task to saccade to a colour singleton in a visual search paradigm. Consistent with the view that capture can be modulated by stimulus expectancies, the rate of oculomotor capture declined across repeated presentations of the onset distractor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining the interplay between voluntary and involuntary saccades have found that an abrupt onset of an irrelevant visual stimulus causes a reliable distraction effect (Irwin, Colcombe, Kramer, & Hahn, 2000;Ludwig & Gilchrist, 2002;Schreij, Owens, & Theeuwes, 2008;Theeuwes, Kramer, Hahn, Irwin, & Zelinsky, 1999). On 20-50% of such trials distractors cause an involuntary saccade towards the distractor (Godijn & Theeuwes, 2002;Irwin et al, 2000;Ludwig & Gilchrist, 2002), although some habituation has also been observed (Godijn & Kramer, 2008). Motion and motion onset has also been shown to be a potent capturer of attention in object detection paradigms (Abrams & Christ, 2003;Al-Aidroos, Guo, & Pratt, 2010;Franconeri & Simons, 2005;Guo, Abrams, Moscovitch, & Pratt, 2010).…”
Section: Introductionmentioning
confidence: 99%